Building Effective Online Marketplaces with Institution-Based Trust - Pavlou, Paul A.; Gefen, David (Information Systems Research, 2004)
Institution-based trust is a buyer’s perception that effective third-party institutional mechanisms are in place to facilitate transaction success. This paper integrates sociological and economic theories about institution-based trust to propose that the perceived effectiveness of three IT-enabled institutional mechanisms–specifically feedback mechanisms, third-party escrow services, and credit card guarantees–engender buyer trust in the community of online auction sellers. Trust in the marketplace intermediary that provides the overarching institutional context also builds buyer’s trust in the community of sellers. In addition, buyers’ trust in the community of sellers (as a group) facilitates online transactions by reducing perceived risk. Data collected from 274 buyers in Amazon’s online auction marketplace provide support for the proposed structural model. Longitudinal data collected a year later show that transaction intentions are correlated with actual and self-reported buyer behavior. The study shows that the perceived effectiveness of institutional mechanisms encompasses both “weak” (market-driven) and “strong” (legally binding) mechanisms. These mechanisms engender trust, not only in a few reputable sellers, but also in the entire community of sellers, which contributes to an effective online marketplace. The results thus help explain why, despite the inherent uncertainty that arises when buyers and sellers are separated in time and in space, online marketplaces are proliferating. Implications for theory are discussed, and suggestions for future research on improving IT-enabled trust-building mechanisms are suggested.